2016
DOI: 10.1016/j.tplants.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Linking Metabolism to Membrane Signaling: The GABA–Malate Connection

Abstract: γ-Aminobutyric acid (GABA) concentration increases rapidly in tissues when plants encounter abiotic or biotic stress, and GABA manipulation affects growth. This, coupled to GABA's well-described role as a neurotransmitter in mammals, led to over a decade of speculation that GABA is a signal in plants. The discovery of GABA-regulated anion channels in plants provides compelling mechanistic proof that GABA is a legitimate plant-signaling molecule. Here we examine research avenues unlocked by this finding and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 64 publications
2
56
0
Order By: Relevance
“…Given that EBCs represent about a quarter of the total leaf volume (see the preceding texts), the estimated concentration of GABA in EBC should be therefore at least 10‐fold higher than in brushed leaf blade, that is about 5–6 m m . This is clearly within the physiological range for reported effects of GABA on ion channels activity in plants (Shabala et al ,b; Ramesh et al ; Gilliham and Tyerman ) and can therefore modulate salt loading into EBC, as shown in Fig. .…”
Section: Discussionsupporting
confidence: 84%
“…Given that EBCs represent about a quarter of the total leaf volume (see the preceding texts), the estimated concentration of GABA in EBC should be therefore at least 10‐fold higher than in brushed leaf blade, that is about 5–6 m m . This is clearly within the physiological range for reported effects of GABA on ion channels activity in plants (Shabala et al ,b; Ramesh et al ; Gilliham and Tyerman ) and can therefore modulate salt loading into EBC, as shown in Fig. .…”
Section: Discussionsupporting
confidence: 84%
“…In parallel, as we have argued, once we have gained a more complete understanding of the exact function of the metabolites themselves, in a range of tissues and cellular circumstances, adoption of synthetic biology approaches may prove a more effective way of rationally engineering their levels. While the synthetic biology approach may well circumvent problems associated with feedback regulation of the plants’ native enzymes, another aspect that will need a great deal of attention is the fact that several of the intermediates of, or intimately related to, the TCA cycle have recently been demonstrated to have signaling functions (Finkemeier et al ; Timm et al ; Gilliham and Tyerman ). Bearing this in mind, the idea of expressing synthetic metabolons may well ultimately represent the best practice for engineering plant metabolism with as great a precision as possible.…”
Section: Conclusion and Future Prospects At Modifying Plant Productimentioning
confidence: 99%
“…Detailed information on metabolism and functions of GABA in plants was described in an earlier review (Shelp and others 1999). In recent years, the role of GABA as a signal molecule in plant tissue has also been reported (Bouché and Fromm 2004;Ramesh and others 2015;Gilliham and Tyerman 2016).…”
mentioning
confidence: 78%
“…Several scientific studies have shown evidence that GABA plays a key role in multiple physiological processes in plants such as carbon and nitrogen metabolism, cytosolic pH regulation, nitrogen storage, defense against pests, plant microbe interactions, protection against oxidative stress, osmotic regulation, as well as normal growth and development (Shelp and others 1999;Bouché and Fromm 2004;Gilliham and Tyerman 2016). Detailed information on metabolism and functions of GABA in plants was described in an earlier review (Shelp and others 1999).…”
mentioning
confidence: 99%